Developmental characteristics of loess mudflow and correlation analysis with influencing factors - Wang, Bo; Zhao, Zhi hai; Huang, Xin; Gu, Gang; Du, Xing hua; Yang, Yong (Frontiers in Earth Science, 2024)
Loess mudflow is a unique geological hazard in the Loess Plateau, presenting a significant risk to the lives and properties of the region's inhabitants. Defining and categorizing loess mudflow scientifically, as well as comprehending their disaster-prone environment and patterns of development, are crucial for implementing effective disaster prevention and mitigation strategies. Based on extensive field investigations and statistical analyses, this study defines and categorizes the loess mudflow into five types: liquefaction flow, freeze-thaw creep, subsurface erosion failure, collapse-mudflow, and erosion-enlargement. Statistical analysis reveals that the drainage area of loess mudflow is mostly concentrated between 0.15-30 km 2 , the bed slope typically ranges from 10-200‰, material storage in channels is mostly above 5×10 4 m 3 /km 2 , and the rainfall intensity triggering mudflow formation is generally greater than 10 mm/h; furthermore, a correlation analysis between the parameters of loess mudflow and the influencing factors reveals a significant linear growth relationship between mudflow volume and drainage area, and also reveals a significant power function relationship with the increase in channel bed slope. However, there is no significant correlation between mudflow volume and solid material storage, and mudflow density shows no significant correlation with drainage area, channel bed slope, or solid material storage. Finally, an empirical formula for estimating mudflow volume is proposed through regression analysis. The research findings aim to provide a theoretical basis for the study and risk assessment of loess mudflow disasters.